The structural adjustment programme and Nigeria's agricultural development - Ihimodu, Ifeyori I.; National Centre for Economic Management and Administration (Nigeria) (Ibadan, Nigeria : National Centre for Economic Management and Administration, 1993)
This study aim at examine the role of Agriculture in the structural imbalance of the Nigerian economy. It also examine the direct and indirect focus of policy instruments of ASAP on Agriculture.
Includes bibliographical references (p. 97-98).
hza 19/02/2019
Loans
Keywords: Agriculture and state; Agriculture; Structural adjustment (Economic policy); Nigeria